PERLINDUNGAN HAM PEKERJA MIGRAN: KAJIAN NORMATIF KEWAJIBAN INDONESIA BERDASAR PRINSIP-PRINSIP DAN NORMA-NORMA HUKUM INTERNASIONAL - Rahayu, Sri Lestari; Muslimah, Siti; Sasmini, Sasmini (Faculty of Law, Universitas Sebelas Maret, 2013)
AbstractThis research is conducted to get a legal argumentation related to responsibility of Indonesia on protection of its citizen, especially migrant workers. The question will be answered by determining the norms and principles that underlie Indonesia in protecting the human rights of its citizens. The sources of this research are international conventions, customary international law, doctrine, legal instruments in Indonesia and some of publications concerning the state responsibility to protect migrant workers. The legal sources collected by study documentation are analyzed by interpretation and content analysis. The results show that the general legal principles in which become basic of Indonesia associated with its obligation to provide protection of human rights of women migrant workers are based on the principle of nationality/citizenship of Indonesia, the principle of pacta sunt servanda, the principle of exhaustion of local remedies, the shift in meaning of the sovereignty principle and recognition principles theory of natural rights which inherent in every human being. While the norms are contained in the Migration for Employment Convention (Revised), 1949 (No. 97), the Convention on Migrant Workers (Supplementary Provisions), 1975 (No. 143), United Nations Convention on the Protection of the Rights of All Migrant Workers and Members of Their Families 1990.Key words: human rights, migrant workers, obligations, international lawAbstrakPenelitian ini dilakukan untuk memperolah gambaran yang lebih mendalam mengenai tanggung jawab Negara Indonesia dalam memberikan perlindungan terhadap hak-hak warga negaranya, khususnya pekerja migran. Penulis mencoba menjawab permasalahan tersebut dari sisi normatif yaitu dengan mendasarkan pada norma-norma dan prinsip-prinsip yang mewajibkan setiap negara termasuk Indone- sia untuk melindungi hak asasi warga negaranya. Bahan penelitian yang digunakan meliputi perjanjian- perjanjian internasional, doktrin, hukum kebiasaan internasional, peraturan perundang-undangan di Indonesia, serta beberapa publikasi yang terkait dengan kewajiban negara atas perlindungan pekerja migran. Bahan hukum yang dikumpulkan melalui studi dokumen selanjutnya dianalisis melalui interpretasi teks dan analisis isi. Hasil pembahasan menunjukkan bahwa prinsip-prinsip hukum umum yang menjadi dasar Indonesia terkait dengan kewajibannya untuk memberikan perlindungan HAM pekerja migran didasarkan pada prinsip nasionalitas, prinsip pacta sunt servanda, prinsip exhaustion of local remedies, pergeresan makna prinsip kedaulatan dan diakuinya prinsip teori hak-hak kodrati yang melekat dalam diri setiap manusia. Sedangkan norma-normanya terdapat dalam Konvensi Migrasi untuk Pekerjaan (Revisi), 1949 (No. 97), Konvensi Pekerja Migran (Ketentuan-Ketentuan Tambahan), 1975 (No. 143), United Nations Convention on The Protection of The Rights of All Migran Workers and Member of Their Families tahun 1990.Kata kunci: hak asasi manusia (HAM), pekerja migran, kewajiban, hukum internasional